Turning to stone : discovering the subtle wisdom of rocks - Bjornerud, Marcia (Flatiron Books, 2024)
"Rocks are the record of our creative planet reinventing itself for four billion years. Nothing is ever lost, just transformed. Marcia Bjornerud's life as a geologist has coincided with an extraordinary period of discovery. From an insular girlhood in rural Wisconsin, she found her way to an unlikely career studying mountains in remote parts of the world. As one of few women in her field, she witnessed the shift in our understanding of the Earth, from solid object to an entity in a constant state of transformation. In the most tumultuous times of her own life, a deep understanding of our rocky planet imbued her life with meaning. The lives of rocks are long and complex, spanning billions of years and yet shaping our own human lives in powerful, invisible ways. Sandstone that filters out pathogens creating underground oases in aquifers of clean water. Ecologite is "the chosen rock" whose formation keeps the planet running. Earth is not just a passive backdrop, or a source of resources to be mined, extracted, and carved out. Rocks are full of wisdom, but somewhere along the way many of us have forgotten how to hear it. When we are uncertain about where to find truth, a geocentric worldview reminds us that we are Earthlings, part of a planetary community where we can find wisdom in the most unlikely places"--